Monanchocidin A From Subarctic Sponges of the Genus Monanchora and Their Promising Selectivity Against Melanoma in vitro - Gogineni, Vedanjali; Oh, Joonseok; Waters, Amanda L.; Kelly, Michelle; Stone, Robert; Hamann, Mark T. (Frontiers in Marine Science, 2020)
Marine sources have long been known for their potential to produce unique skeletons and various biological activities. Fractionation of the ethanol extracts of an undescribed species of Monanchora Carter, 1883 and a specimen closely comparable to Monanchora pulchra (Lambe, 1895) (Class Demospongiae, Order Poecilosclerida, Family Crambeidae), yielded a known compound, monanchocidin A. Monanchocidin A, a secondary metabolite, showed potent selective activity for the melanoma panel in the NCI cancer cell screening panel.